2019
DOI: 10.7759/cureus.4353
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in the Prevalence of Diabetes Decompensation (Diabetic Ketoacidosis and Hyperosmolar Hyperglycemic State) Among Adult Patients Hospitalized with Diabetes Mellitus: A Nationwide Analysis Stratified by Age, Gender, and Race

Abstract: Background Disproportionate change in the burden of diabetes mellitus across various subgroups has been reported in the United States. However, changing landscape of the prevalence and mortality of decompensated diabetes (diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic state (HHS)) remains indistinct across various age, gender, and racial groups of hospitalized diabetics. Methods The National Inpatient Sample (NIS) datasets (2007-2014) were sought to assess the prevalence and temporal trends in deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
(40 reference statements)
1
15
2
Order By: Relevance
“…The prevalence of DKA in patients with diabetes in our cohort was substantially higher than the 0.9% prevalence of hyperglycemic emergency (encompassing DKA, and the related hyperosmolar hyperglycemic state) in patients hospitalized for all causes in National Inpatient Sample (NIS) datasets [14] . Patients with diabetes who developed DKA were younger (64 vs. 69 years old), had higher levels of HbA1c, and had fewer chronic medical conditions (14% with CKD, 63.7% with HTN and 10.8% with pulmonary disease, as compared to 22.8%, 84% and 19.8% respectively) as compared to patients with diabetes and without DKA.…”
Section: Discussioncontrasting
confidence: 54%
“…The prevalence of DKA in patients with diabetes in our cohort was substantially higher than the 0.9% prevalence of hyperglycemic emergency (encompassing DKA, and the related hyperosmolar hyperglycemic state) in patients hospitalized for all causes in National Inpatient Sample (NIS) datasets [14] . Patients with diabetes who developed DKA were younger (64 vs. 69 years old), had higher levels of HbA1c, and had fewer chronic medical conditions (14% with CKD, 63.7% with HTN and 10.8% with pulmonary disease, as compared to 22.8%, 84% and 19.8% respectively) as compared to patients with diabetes and without DKA.…”
Section: Discussioncontrasting
confidence: 54%
“…Although smoking remains a widely reported CVD risk factor for worse outcomes, it did not play a role in predicting short-term outcomes for frail patients in our study. The rising burden of endocrine disorders, including diabetes mellitus and hypothyroidism among the US population, is known to play a role in PCI outcomes [19]. However, in our study, we did not observe a correlation between diabetes or hypothyroidism and in-hospital negative outcomes in frail patients.…”
Section: Discussioncontrasting
confidence: 89%
“…HHS is recognized as an emerging issue in children and young adults (14). Other studies using NIS have found similar increases in hyperglycemic crisis events but use different denominators (15,16). Our study is unique in that we report rates by the population with diagnosed diabetes, which accounts for changes in diabetes epidemiology over time.…”
Section: Discussionmentioning
confidence: 92%